Women’s Economic Empowerment through Agriculture: Analyzing Barriers and Solutions - Fayaz Gul Mazloum Yar; Ezat Ullah Sail (Edunity Kajian Ilmu Sosial dan Pendidikan, 2025)
This research focuses on the challenges faced by women in Afghanistan with regard to economic empowerment, particularly in the agricultural sector. This sector is critical to the country's economy, but women remain marginalized despite contributing significantly. Various barriers, including limited access to resources and cultural norms, hinder their participation. The purpose of this study is to analyze the barriers women face in the agricultural sector in Afghanistan and propose practical solutions to enhance their economic empowerment. The methods used in this study included a mixed approach, with structured surveys to collect quantitative data and semi-structured interviews and focus group discussions to gain qualitative insights. Data from different regions in Afghanistan were analyzed to identify important patterns affecting women's participation. The results showed that cultural, economic, educational and political barriers strongly influence women's empowerment. Most respondents reported difficulties in accessing financial resources and agricultural training. However, there are opportunities through non-governmental organization support and sustainable agricultural practices that can improve women's economic status. This research emphasizes the importance of overcoming these barriers to increase women's participation in agriculture. By providing education, access to resources, and legal support, women can be economically empowered, which in turn will contribute to the growth of the agricultural sector and sustainable development in Afghanistan.